An investigation into the role played by perceived security concerns in the adoption of mobile money services : a Zimbabwean case study - Madebwe, Charles (Rhodes University, Faculty of Science, Department of Computer Science, 2015)
The ubiquitous nature of mobile phones and their popularity has led to opportunistic value added services (VAS), such as mobile money, riding on this phenomenon to be implemented. Several studies have been done to find factors that influence the adoption of mobile money and other information systems. The thesis looks at factors determining the uptake of mobile money over cellular networks with a special emphasis on aspects relating to perceived security even though other factors namely perceived usefulness, perceived ease of use, perceived trust and perceived cost were also looked at. The research further looks at the security threats introduced to mobile money by virtue of the nature, architecture, standards and protocols of Global System for Mobile Communications (GSM). The model employed for this research was the Technology Acceptance Model (TAM). Literature review was done on the security of GSM. Data was collected from a sample population around Harare, Zimbabwe using physical questionnaires. Statistical tests were performed on the collected data to find the significance of each construct to mobile money adoption. The research has found positive correlation between perceived security concerns and the adoption of money mobile money services over cellular networks. Perceived usefulness was found to be the most important factor in the adoption of mobile money. The research also found that customers need to trust the network service provider and the systems in use for them to adopt mobile money. Other factors driving consumer adoption were found to be perceived ease of use and perceived cost. The findings show that players who intend to introduce mobile money should strive to offer secure and useful systems that are trustworthy without making the service expensive or difficult to use. Literature review done showed that there is a possibility of compromising mobile money transactions done over GSM
Keywords: Banks and banking, Mobile -- Zimbabwe; Global system for mobile communications; Cell phones -- Security measures